Container Gardens for Outdoor Spaces - Gary W. Knox (EDIS, 2008)
ENH-1095, a 7-page illustrated fact sheet by Gary W. Knox, provides homeowners with information about the design and use of container gardens, plant selection, how to plant and how to maintain the plantings. Published by the UF Department of Environmental Horticulture, February 2008.